Pendampingan Bahasa dan Optimalisasi Promosi Desa Wisata Punten Batu di Media Sosial - Dita Grace; Didik Hartono; Caterine Widya Perdhani; Ardafa Rizko Ubadillah; Indriyani Anisa (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
Abstract The development of tourism villages in Indonesia is greatly needed through social media promotion. Sosial Tourist village has potential to developing by using social media promotion. Through social media which are recently booming, such as Instagram, Facebook and Tiktok, this study focused on the people under 40 years old. Some social media are very impressived with content writing technique as potential to developing ecotourism for boarding the language and its promotion. This study attracted village promotion by using social media, which using content writing technique in conference. The potential using content writing technique in conference with village tourist community gave point of views, such as: realized different platform and website in putting information, identified the media social users, showed a good written from local language and Indonesian language, and used the hastag as promtion and upgrading the traffic. By conference for assisting and optimalization language used, the promoting of tourist village Desa Wisata Punten Batu on social media are more interesting to read by traveller.